A Microscale–Optical Interface to Examine Electric Field-Induced Cell Motility Within Whole-Eye Facsimiles - Sakshi Koul; Luke A. Devecka; Mark C. Pierce; Maribel Vazquez (Micro)
Microscale systems have been underexplored in contemporary regenerative therapies developed to treat vision loss. The pairing of in vitro cell systems with optical fluorescent imaging provides unique opportunities to examine the infiltration of donor stem cells needed for successful transplantation therapies. A parallel eye device was developed to provide electric field (EF) stimulation to guide the migration of cells within 3D eye facsimiles synthesized from different ocular biomaterials. Cell infiltration within facsimiles was rapidly resolved using confocal microscopy to eliminate dependence on the cryostat sectioning commonly used for cell study. Moreover, EF stimulated galvanotaxis of donor cells within different depths of eye facsimiles. Optical imaging provided rapid resolution of z-stack images at physiologically appropriate depths below 500 microns. This study demonstrates that paired microscale–optical systems can be developed to elucidate understudied transplantation processes and improve future outcomes in patients.